Assessment and Treatment of Deviant Behavior in Children - Section One Introduction and Project Overview. Final Report - Mattson, Robert H.; Oregon Univ., Eugene ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The procedures and results contained in the report define a program of research designed to investigate methods of assessing and modifying deviant behavior within the educational setting. The report has been divided into six sections with section one providing an introduction and project overview. The basic and interim proposal project commitments are stated and some of the methodological issues and questions generated during the research such as the teacher variable are briefly discussed. An overview and status of the project is provided by reviewing the content of the other five sections of the report. Section two (EC 032 209) deals with assessment; section three (EC 032 210) discusses treatment; section four (EC 032 211) covers generalization and maintenance; section five (EC 032 212) analyzes teacher behavior; and section six (EC 032 213) details the single subject experiments. (CD)
Sponsoring Agency: Bureau of Education for the Handicapped (DHEW/OE), Washington, DC.
Contract Number: OEG-4-6-061308-0571.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Antisocial Behavior; Behavior Change; Behavior Problems; Classroom Techniques; Emotional Disturbances; Exceptional Child Research; Research Design; Research Projects